Zero thermal expansion in NaZn13-type La(Fe, Si)13 compounds. Issue 4 (15th December 2014) - Wang, Wei; Huang, Rongjin; Li, Wen; Tan, Jie; Zhao, Yuqiang; Li, Shaopeng; Huang, Chuanjun; Li, Laifeng
Abstract : The La(Fe, Si)13 -based compounds were successfully modified into continuous zero thermal expansion (ZTE) materials by optimizing the chemical composition. Abstract : A zero thermal expansion material in a pure form of NaZn13 -type La(Fe, Si)13 was fabricated. Through optimizing the chemical composition, an isotropic zero thermal expansion material is achieved. The obtained materials exhibit a low expansion of | α | < 1.0 × 10 −6 K −1 ( α is the coefficient of linear thermal expansion) over a broad temperature range (15–150 K). The present study indicates that the thermal expansion behavior of the NaZn13 -type La(Fe, Si)13 compounds depends mainly on the content of Si element. This new material is desirable in many fields of industry as a reliable and low-cost zero thermal expansion material.